Respostas

2013-05-27T23:43:57-03:00

x - y = 1    

x + y = 9    ------> y = 9 - x ------> y = 9 - 5 --------> y = 4

----------

2x = 10

x = 10 / 2

x = 5

  • Usuário do Brainly
2013-05-27T23:44:39-03:00

Segundo o enunciado, podemos montar o sistema:

 

\begin{cases} \text{x}-\text{y}=1 \\ \text{x}+\text{y}=9 \end{cases}

 

Somando as equações, obtemos:

 

(\text{x}-\text{y})+(\text{x}+\text{y})=1+9

 

2\text{x}=10

 

Donde, segue:

 

\text{x}=5

 

Desta maneira, temos:

 

\text{y}=9-5=4

2 2 2